Systematic review of the effectiveness of breathing retraining in asthma management. (December 2011) - Burgess, John; Ekanayake, Buddhini; Lowe, Adrian; Dunt, David; Thien, Francis; Dharmage, Shyamali C
In asthma management, complementary and alternative medicine is enjoying a growing popularity worldwide. This review synthesizes the literature on complementary and alternative medicine techniques that utilize breathing retraining as their primary component and compares evidence from controlled trials with before-and-after trials. Medline, PubMed, Cumulative Index to Nursing and Allied Health Literature and the Cochrane Library electronic databases were searched. Reference lists of all publications were manually checked to identify studies not found through electronic searching. The selection criteria were met by 41 articles. Most randomized controlled trials (RCTs) of the Buteyko breathing technique demonstrated a significant decrease in ββ2 -agonist use while several found improvement in quality of life or decrease in inhaled corticosteroid use. Although few in number, RCTs of respiratory muscle training found a significant reduction in bronchodilator medication use. Where meta-analyses could be done, they provided evidence of benefit from yoga, Buteyko breathing technique and physiotherapist-led breathing training in improving asthma-related quality of life. However, considerable heterogeneity was noted in some RCTs of yoga. It is reasonable for clinicians to offer qualified support to patients with asthma undertaking these breathing retraining techniques.